2017
DOI: 10.3390/foods6120112
|View full text |Cite
|
Sign up to set email alerts
|

Milk Technological Properties as Affected by Including Artichoke By-Products Silages in the Diet of Dairy Goats

Abstract: Traditional farming practices include the use of local agricultural by-products in the diet of ruminants. Artichoke harvesting and transformation yield high amounts of by-products that, if properly used, may reduce farming costs and the environmental impact of farming. The present study tests the inclusion of silages from artichoke by-products (plant and outer bracts) in the diet of dairy goats (0%, 12.5% and 25% inclusion) on the technological and sensory properties of milk during a five-month study. Milk com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…In this way, it was possible to feed the animals with silage in optimal conditions that would not have been affected by aerobic degradation. The composition of the rations was determined in a similar way to Monllor et al and Monllor et al [19,20], using Association of Official Agricultural Chemists (AOAC) methods [25] for dry matter (DM, g/kg; method 930.5), organic matter (OM, g/kg DM; method 942.05), ether extract (EE, g/kg DM; method 920.39) and crude protein (CP, g/kg DM; method 984.13). The contents of neutral detergent fibre (NDF, g/kg DM), acid detergent fibre (ADF, g/kg DM) and acid detergent lignin (ADL, g/kg DM) were analysed according to Van Soest et al [26].…”
Section: Variables Analysedmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, it was possible to feed the animals with silage in optimal conditions that would not have been affected by aerobic degradation. The composition of the rations was determined in a similar way to Monllor et al and Monllor et al [19,20], using Association of Official Agricultural Chemists (AOAC) methods [25] for dry matter (DM, g/kg; method 930.5), organic matter (OM, g/kg DM; method 942.05), ether extract (EE, g/kg DM; method 920.39) and crude protein (CP, g/kg DM; method 984.13). The contents of neutral detergent fibre (NDF, g/kg DM), acid detergent fibre (ADF, g/kg DM) and acid detergent lignin (ADL, g/kg DM) were analysed according to Van Soest et al [26].…”
Section: Variables Analysedmentioning
confidence: 99%
“…Only three studies have been published about its use in dairy goats. Muelas et al [18] observed that the inclusion of artichoke plant silage of up to 25% in the diet had no effect on the sensory properties of yogurt made from the milk of these animals, while Monllor et al and Monllor et al [19,20] observed that the inclusion of up to 40% of artichoke plant silage and broccoli by-product in the middle stage of lactation (fourth to fifth month) had no relevant effects on the milk yield, composition and technological properties, whereas the inclusion of 60% of the by-product reduced performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the CIELAB color coordinates, coordinates a* and b* depend on the natural pigment concentration of goat's milk. [37] Therefore, L* value depends on the dispersion of casein micelles and fat globules that affect the diffusion of the incident light. [38] In the study by Znamirowska et al [31] , fermented milk fortified with magnesium and calcium lactate gave a significantly darker color than the control ones.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…The references found in the literature on the effect of silage consumption of these by-products in sheep on the milk quality and composition and the health status of the animals are scarce, but indicate their suitability for this purpose [1,[4][5][6]. However, there has only been one study conducted in dairy goats on the effect on the technological properties of milk [7].…”
Section: Introductionmentioning
confidence: 99%